The proposed future infrastructure model for basic occupational health services in Malaysia - Samsuddin, Niza; Razali, Ailin; A. Rahman, Nor Azlina; Yusof, Muhammad Zubir; Nik Mahmood, Nik Ahmad Kamal; Abdullah Hair, Ahmad Fitri (USM, 2019)
The objectives of occupational health services (OHS) are to create a healthy and safe working environment, prevent work-related diseases, optimise employees’ functional capacity and promote health. According to the literature, global accessibility to OHS has not shown much improvement and even worsened in certain countries. The main challenges come from the small and medium enterprises (SMEs). To respond to these global challenges, the basic occupational health services (BOHS) guideline was published under the purview of the World Health Organization and the International Labour Organization. The guideline describes BOHS as part of the infrastructure called the occupational safety and health system, an essential element that ensures the high service coverage and sustainability of the programme. The BOHS guideline was introduced in Malaysia by the Department of Occupational Safety and Health with a focus on SMEs, but its accessibility is low. A gap analysis was conducted between the current BOHS in Malaysia and the published international guideline. The important challenges identified that contributes to the low BOHS accessibility in Malaysia is the weakness in the BOHS infrastructure and OHS system provision. The proposed BOHS infrastructure model is meant to increase accessibility and to provide fair and equitable health services for Malaysians.